1996
DOI: 10.1152/ajpheart.1996.271.5.h1970
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in lung ischemia and reperfusion injury

Abstract: We studied the effects of nitric oxide synthase (NOS) inhibitors and nitric oxide (NO.) donors on ischemia-reperfusion (I/R)-induced microvascular permeability increase in isolated buffer-perfused rat lungs. Microvascular permeability (Kf,c) was significantly increased in lungs subjected to 45 min of ischemia followed by 30 min of reperfusion. Lungs that were pretreated with 300 and 600 microM N omega-nitro-L-arginine methyl ester (L-NAME), 1, 300, and 600 microM NG-monomethyl-L-arginine (L-NMMA), or 600 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 0 publications
2
19
0
2
Order By: Relevance
“…However, this is only the case on the vascular side of the lung: several papers have suggested that inhaling NO is beneficial in preventing LIRI (139,204). However, it should be noted that none of these studies provide, nor prove, a mechanism of action for these effects.…”
Section: Mechanisms Of Lung Injury During Irmentioning
confidence: 99%
“…However, this is only the case on the vascular side of the lung: several papers have suggested that inhaling NO is beneficial in preventing LIRI (139,204). However, it should be noted that none of these studies provide, nor prove, a mechanism of action for these effects.…”
Section: Mechanisms Of Lung Injury During Irmentioning
confidence: 99%
“…During NO synthesis by NOS, if L-arginine levels decrease or consumption of NO increases via cell-free plasma hemoglobin and ROS, then oxidative damage occurs, HbS denatures, and superoxide production increases. It was shown that iNOS inhibition significantly limits tissue ischemiareperfusion injury in the liver and kidneys [10][11]; however, inhibition of iNOS attenuated ischemiareperfusion injury in the rat heart [12], but not in the rat lung [13]. Increased iNOS expression was reported in the kidneys of transgenic mice [9], but Nath et al [14] reported the lack of iNOS upregulation in intrarenal vasculature and increased iNOS expression in the glomeruli and distal tubules of sickle mice.…”
Section: Discussionmentioning
confidence: 99%
“…Increased iNOS expression and a consequent increase in tissue nitrite and nitrate production have been observed in the kidneys and liver of SCD patients [8], mice [2,3,8,9], and pigs [4]. Additionally, it was shown that iNOS inhibition significantly limits tissue ischemia-reperfusion injury in the liver and kidneys [10,11]; however, inhibition of iNOS attenuated ischemia-reperfusion injury in the rat heart [12] and did not affect ischemia-reperfusion injury in the rat lung [13]. Increased levels of iNOS expression were shown in the kidneys of transgenic mice [9], but Nath et al [14] reported the lack of upregulation of iNOS in the intrarenal vasculature and increased expression of iNOS in the [15][16][17] and in vitro [18].…”
Section: Introductionmentioning
confidence: 99%
“…At nanomolar concentrations, NO modulates a number of physiologic processes related to vascular reactivity and platelet function [228,269], leukocyte-endothelial cell interactions [270], vascular permeability [271,272], and is cytoprotective in ischemia-reperfusion injury [273,274]. However, at higher micromolar concentrations, NO as well as PN, participates in cellular injury as seen in the lung [243], following the development of ischemia-reperfusion injury, endotoxic and hypovolemic shock [7,275].…”
Section: Protective Effect Of Peroxynitrite In Ischemia Reperfusion Imentioning
confidence: 99%